2008
DOI: 10.1099/mic.0.2008/021188-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug efflux pump overexpression in Staphylococcus aureus after single and multiple in vitro exposures to biocides and dyes

Abstract: Biocides and dyes are commonly employed in hospital and laboratory settings. Many of these agents are substrates for multiple-drug resistance (MDR)-conferring efflux pumps of both Gram-positive and Gram-negative organisms. Several such pumps have been identified in Staphylococcus aureus, and mutants overexpressing the NorA and MepA MDR pumps following exposure to fluoroquinolones have been identified. The effect of exposure to low concentrations of biocides and dyes on the expression of specific pump genes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 36 publications
(33 reference statements)
6
90
0
Order By: Relevance
“…Huet et al demonstrated that in S. aureus, sin-296 gle as well as multiple step-exposure to biocides, which were comparable to CH, resulted in 297 an increase in the MIC for CH and multiple other biocides mostly due to an upregulation of 298 the gene expression of different MDR efflux pumps like mepA and norA [32]. These results 299…”
supporting
confidence: 54%
“…Huet et al demonstrated that in S. aureus, sin-296 gle as well as multiple step-exposure to biocides, which were comparable to CH, resulted in 297 an increase in the MIC for CH and multiple other biocides mostly due to an upregulation of 298 the gene expression of different MDR efflux pumps like mepA and norA [32]. These results 299…”
supporting
confidence: 54%
“…The same approach was used to quantitate mepR expression in strains found to overexpress mepA in conjunction with a MepR substitution mutation (Table 2). qRT-PCR data for the 2005 strain set and selected in vitro-generated mepA-overexpressing mutants have been reported previously (10)(11)(12). For in vitro-derived mutants, the same procedures were used with the exception that gene expression was normalized to that in the appropriate parent strain.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical isolates of S. aureus (one per patient) were collected in 2005 and again in 2009 from the microbiology laboratories of the Detroit Medical Center and the John D. Dingell VA Medical Center in Detroit, MI (n ϭ 232 and 243, respectively). The 2005 strain set has been described previously, as have in vitro-derived mutants of selected strains from this set found to overexpress mepA (10,12). Another 446 unique clinical isolates were collected from centers in Boston, MA, Houston, TX, Omaha, NE, and Freiberg, Germany, in 2009 (14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations